QUANTITATIVE CHARACTERISTICS OF THE RESULTS OF CROSSING KAMPUNG SUPER CHICKENS WITH ARAB CHICKENS UP TO 2 MONTHS OF AGE - M., SAMIUN; ., DEPISON; ., GUSHAIRIYANTO (Majalah Ilmiah Peternakan; Vol 26 No 2 (2023): Vol. 26 No. 2 (2023), 2024)
This study aims to determine the relationship of egg characteristics, quantitative characteristics of the crossing results of Super and Arabian chickens. The research material was 91 Supra chickens consisting of 43 males and 48 females. The method used was experimental observation method. Data collected on egg characteristics, BW, PBB, and body size were analyzed using t-test. The relationship between variables was analyzed by regression and corre- lation. T2-Hotelling analysis was used to compare the body size vectors of male and female Supra chickens. Prin- cipal Component Analysis was used to determine the determinants of the size and shape of male and female Supra chickens. The results of this study showed that the characteristics of eggs, body weight, body weight gain and body size of male Supra chickens were significantly different (P < 0.05) higher than female Supra chickens. Conclusion: The relationship between egg size and egg weight is positive, the closest correlation between sizes and egg weight is egg width. Body weight, body weight gain and body size of male Supra chickens were higher than females. The characteristics of body size in male and female Supra chickens are chest circumference, while the characteristics of body shape are wing length.